Wheat-Maize Intercropping With Reduced Tillage and Straw Retention: A Step Towards Enhancing Economic and Environmental Benefits in Arid Areas - Yin, Wen; Guo, Yao; Hu, Falong; Fan, Zhilong; Feng, Fuxue; Zhao, Cai; Yu, Aizhong; Chai, Qiang (Frontiers in Plant Science, 2018)
Intercropping is considered a promising system for boosting crop productivity. However, intercropping usually requires higher inputs of resources that emit more CO2. It is unclear whether an improved agricultural pattern could relieve this issue and enhance agricultural sustainability in an arid irrigation area. A field experiment using a well-designed agricultural practice was carried out in northwest China; reduced tillage, coupled with wheat straw residue retention measures, they were integrated with a strip intercropping pattern. We determined the crop productivity, water use, economic benefits, and carbon emissions. The wheat-maize intercropping coupled with straw covering (i.e., NTSI treatment), boosted grain yield by 27 to 38% and 153 to 160% more than the conventional monoculture of maize and wheat, respectively, increased by 9.9 to 11.9% over the conventional intercropping treatment. Similarly, this pattern also improved water use efficiency by 15.4 to 22.4% in comparison to the conventional monoculture of maize, by 45.7 to 48.3% in comparison to the conventional monoculture of wheat, by 14.7 to 15.9% in comparison to the conventional intercropping treatment. Meanwhile, NTSI treatment caused 7.4 to 13.7% and 37.0 to 47.7% greater solar energy use efficiency than the conventional monoculture of maize and wheat, respectively. Furthermore, the NTSI treatment had a higher net return by 54 to 71% and 281 to 338% and a higher benefit per cubic meter of water by 35 to 51% and 119 to 147% more than the conventional monoculture of maize and wheat, respectively. Similarly, it increased the net return and benefit per cubic meter of water by 8 to 14% and 14 to 16% in comparison to the conventional intercropping treatment, respectively. An additional feature of NTSI is that it reduced carbon emissions by 13.4 to 23.8% and 7.3 to 17.5% while improving carbon emission efficiency by 62.6 to 66.9% and 23.2 to 33.2% more than the conventional monoculture maize and intercropping treatments, respectively. We can draw a conclusion that intercropping maize and wheat, with a straw covering soil surface, can be used to enhance crop production and net returns while effectively lowering CO2 emissions in arid oasis irrigation region.